2x^2-10x+18=0

Simple and best practice solution for 2x^2-10x+18=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x^2-10x+18=0 equation:


Simplifying
2x2 + -10x + 18 = 0

Reorder the terms:
18 + -10x + 2x2 = 0

Solving
18 + -10x + 2x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '2'.
2(9 + -5x + x2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(9 + -5x + x2)' equal to zero and attempt to solve: Simplifying 9 + -5x + x2 = 0 Solving 9 + -5x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-9' to each side of the equation. 9 + -5x + -9 + x2 = 0 + -9 Reorder the terms: 9 + -9 + -5x + x2 = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -5x + x2 = 0 + -9 -5x + x2 = 0 + -9 Combine like terms: 0 + -9 = -9 -5x + x2 = -9 The x term is -5x. Take half its coefficient (-2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. -5x + 6.25 + x2 = -9 + 6.25 Reorder the terms: 6.25 + -5x + x2 = -9 + 6.25 Combine like terms: -9 + 6.25 = -2.75 6.25 + -5x + x2 = -2.75 Factor a perfect square on the left side: (x + -2.5)(x + -2.5) = -2.75 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

You can always share this solution

See similar equations:

| 9s^2+3s-20=x | | (x-1)(x^2-4)+2(x-1)(x+2)=(x-1)P | | 9x^2-4.5x-3.5=0 | | 6x^2-5x-14=0 | | x^4-7x-18=0 | | x^2-8x+18=0 | | x^2-8b+18=0 | | 30a^2+am-m^2=0 | | 30a^2+am-m^2=o | | 12s^2+11st-5t^2=0 | | 14x^2+11yx-15y^2=0 | | 3x^2+8=0 | | -2v^2-v+12=-3v^2+6v | | x^2+15x-64=0 | | 2x^2+8x-2=0 | | 12x^2-x-20=0 | | 5x^2+13x+6=0 | | x^3-12x^2+35x=0 | | x^3-13x^2+30x=0 | | 6x^2+17x-45=0 | | x^4-3x^2+1=0 | | 5x^2-5x-3= | | 3x^2-13x+14=0 | | 6x^2+x-c=(cx-1)(3x+2) | | X*x=x^2 | | 9c=c^2 | | 3x^2-12=0 | | 3x^2-8=0 | | x^2+6=6x^2-16 | | 16x^2-25=0 | | .66x^2-36=0 | | .66x^2-32=0 |

Equations solver categories